Kinetics and equilibrium of lanthanum biosorption by free and immobilized microalgal cells - Fernanda do Nascimento Corrêa; Aderval Severino Luna; Antonio Carlos Augusto da Costa (Adsorption Science & Technology)
This work aimed to study the potential for bioremediation of lanthanum by microalgae Ankistrodesmus sp. and Golenkinia sp., as free cells and immobilized in calcium alginate pellets. To reach that goal, studies have been conducted in batch and in continuous fixed bed column. Kinetic models of pseudo-first order and -second order and equilibrium isotherms of Langmuir and Freundlich were used to predict the metal accumulation behavior by free and immobilized biomass in a batch system. The data were best fit to kinetic model of second order, with coefficients of determination (R 2 ) greater than 0.98. Free cells were more efficient in the process than alginate pellets and it was not possible to model the results due to the very fast uptake. Equilibrium modelling indicated that both free and immobilized cells, as well as alginate pellets results were best fit to Langmuir equation due to the high R 2 value and similarity with experimental results. Dynamic column tests conducted with Ankistrodesmus sp. and Golenkinia sp. immobilized cells during 8 hours presented 80% efficiency in the removal of the metal, without reaching saturation. The high and fast ability of the microalgae to adsorb lanthanum corroborates their potential large-scale application.